Loss of the mechanotransducer zyxin promotes a synthetic phenotype of vascular smooth muscle cells - Ghosh, Subhajit; Kollár, Branislav; Nahar, Taslima; Sticht, Carsten; Gretz, Norbert; Wagner, Andreas H.; Korff, Thomas; Hecker, Markus (Journal of the American Heart Association, 2015)
Background Exposure of vascular smooth muscle cells (VSMCs) to excessive cyclic stretch such as in hypertension causes a shift in their phenotype. The focal adhesion protein zyxin can transduce such biomechanical stimuli to the nucleus of both endothelial cells and VSMCs, albeit with different thresholds and kinetics. However, there is no distinct vascular phenotype in young zyxin‐deficient mice, possibly due to functional redundancy among other gene products belonging to the zyxin family. Analyzing zyxin function in VSMCs at the cellular level might thus offer a better mechanistic insight. We aimed to characterize zyxin‐dependent changes in gene expression in VSMCs exposed to biomechanical stretch and define the functional role of zyxin in controlling the resultant VSMC phenotype. Methods and Results DNA microarray analysis was used to identify genes and pathways that were zyxin regulated in static and stretched human umbilical artery-derived and mouse aortic VSMCs. Zyxin‐null VSMCs showed a remarkable shift to a growth‐promoting, less apoptotic, promigratory and poorly contractile phenotype with ≈90% of the stretch‐responsive genes being zyxin dependent. Interestingly, zyxin‐null cells already seemed primed for such a synthetic phenotype, with mechanical stretch further accentuating it. This could be accounted for by higher RhoA activity and myocardin‐related transcription factor‐A mainly localized to the nucleus of zyxin‐null VSMCs, and a condensed and localized accumulation of F‐actin upon stretch. Conclusions At the cellular level, zyxin is a key regulator of stretch‐induced gene expression. Loss of zyxin drives VSMCs toward a synthetic phenotype, a process further consolidated by exaggerated stretch.